PENGARUH INTELLECTUAL CAPITAL, PERTUMBUHAN PERUSAHAAN DAN KAPABILITAS TEKNOLOGI TERHADAP NILAI PERUSAHAAN - Ragil Sandra Pratiwi; R Rosiyana Dewi (STMIK Widuri Jakarta, 2025)
The objective of this study is to ascertain the impact of intellectual capital, company growth, and information technology capabilities on firm value. The sampling method employed was purposive sampling, which yielded a total of 42 companies from the following sectors: cyclical, non-cyclical, and industrial. These companies were listed on the Indonesia Stock Exchange (IDX) between 2016 and 2020. The study employs a purposive sampling method and multiple linear regression with SPSS data test software for testing. The results indicate that intellectual capital has a positive effect on firm value, company growth has a positive effect on firm value, and information technology capabilities have no effect on firm value.